RCVibro System: full description of a custom-made vibratory system and its reliability - Pereira, Marcelo Pinto [UNESP]; Pelicioni, Paulo Henrique Silva; Gobbi, Lilian Teresa Bucken [UNESP] (Elsevier, 2017)
Background The use of local muscle vibration is a promising technique to improve motor performance in people with movement impairments. Majority of studies have failed to properly describe the used system and its reliability, making it difficult to transfer this promising technique to clinical practice. Objective To describe technical details of a custom-made vibratory system (RCVibro System), as well as to determine its reliability and functionality. Methods The vibration frequency and the electric potential difference/vibration frequency curve of six devices were assessed (at the same day and at different days), allowing us to determine the system reliability. In addition, the RCVibro System functionality was analyzed by the center-of-pressure behavior assessment during the tibialis anterior bilateral stimulation in fifteen young people. Results The RCVibro System showed a very-high reliability between assessments within the same day (ICC(2,6) ranging from 0.95 to 0.99; p < 0.01) and between different days (ICC(2,6) ranging from 0.81 to 0.98; p < 0.01). We also observed a forward center-of-pressure displacement (p < 0.01) and an increase in the center-of-pressure velocity (p < 0.01). Conclusion We conclude that RCVibro System is a highly reliable system. The results demonstrate the potential usage of RCVibro System in clinical and research settings. Further investigation is needed in people with motor and neurological disorders.
Keywords: Center-of-pressure; Intraclass correlation coefficient; Physical therapy; Rehabilitation; Reliability; Vibration